Hydrological risk assessment of the Johor River: Flood Frequency Analysis with L-Moments - Othman, Nur Hanida; Badyalina, Basri; Shah Izan, Sheril Haiza; Shabri, Ani Shabri; Marsani, Muhammad Fadhil; Ya'acob, Fatin Farazh (UiTM Cawangan Perlis, 2025)
Flooding remains one of the most significant hydrological hazards in Malaysia, particularly within the Johor River Basin. This study conducts a Flood Frequency Analysis (FFA) using the L-Moment method to identify the most suitable probability distribution for modelling annual maximum streamflow at the Kahang River station. A 45-year dataset (1978-2022) was analyzedusing three candidate distributions: Generalized Logistic (GLO), Generalized Pareto (GPA), and Pearson Type-III (PE3). The L-Moment Ratio Diagram (LMRD), alongside statistical performance metrics such as MAE, RMSE, MAPE, RMSPE, R2and Euclidean Distance was employed to evaluate model accuracy. Results reveal that the GPA distribution provides the best fit as it provides smallest value of MAE, MAPE, RMSPEand Euclidean Distance, demonstrating superior accuracy in predicting extreme flood events, particularly for high return periods. The study offers critical insights for flood risk assessment, infrastructure planning, and early warning system development in the region. Lastly, it provided researchers with flood analysis methods using L-moments and extreme value distributions.